"A pílula da felicidade": a demanda e o consumo de Fluoxetina e suas relações com os imperativos do discurso capitalista - Renato Jose de Avila (2014)
This dissertation intends to investigate, in light of psychoanalysis, the relationship between subject and psychotropic medicine in a mental health clinic of a city in a metropolitan area of Belo Horizonte. Considering the current discussion about the excessive use of medicines nowadays, we use fragments of clinics discussions with doctors that works in the city and fragments of cases of patients under treatment in this clinic. Our question is if the demand and consumption of Fluoxetine by this patients is somehow related with the imperatives of the capitalist speech. We propose that with the alliance between psychiatry and neurosciences there has been a biological understanding of psychic suffering, that led to increasing rates of depression and abuse of pharmacological treatment. Our study seeks as well a historic approach of depression, in the optic of psychiatry, and some possible readings about this in the field of psychoanalysis, with Freud and Lacan. By means of psychoanalysis, and using cases fragments, we interrogate the depression of these subjects that are looking for treatment with Fluoxetine. Finally, we concluded that the demand and consumption of this substance are governed by capitalist speech imperatives, like welfare, productivity and immediate relief of psychic suffering of these subjects.